Synthesis and Adsorption of Alginate and Starch-Based Hydrogels for Cationic Dye from Aqueous Solution: Thermodynamic and Isotherm Modeling Non-linear - Aljeboree, Aseel Mushtaq; Alkaim, Ayad Fadhil (Indonesian Journal of Chemistry, 2024)
This work prepared new eco-friendly biocomposite hydrogels by graft co-polymerization from starch (ST), sodium alginate (SA), acrylamide (AM), and acrylic acid (AC). The performance of starch graft-poly(acrylamide-co-acrylic acid) (ST-g-P(AM-co-AC)) and sodium alginate graft-poly(acrylamide-co-acrylic acid) (SA-g-P(AM-co-AC)) absorbent hydrogels was evaluated for efficient dye removal from aqueous solution due to their unequal network structure and a restricted number of the hydrophilic groups. Adsorption characteristics of the as-prepared hydrogels were tested for methylene blue (MB) as an adsorbate. The removal percentage increases when increased the adsorbent doses of both hydrogels due to the increase of active sites of the hydrogel. The isotherm models and thermodynamic studies of MB dye on hydrogels have been assessed at several conditions like adsorbent dosage, solution temperature, and equilibrium time. The equilibrium results followed the Freundlich model. The thermodynamic parameter indicated that MB dye adsorption on hydrogels was endothermic and spontaneous. On the basis of the obtained result, the hydrogels are environmental and expansive adsorbent that might be a reliable alternative to elimination dyes from aqueous solution.